A Dual-Mode Imaging Nanoparticle Probe Targeting PD-L1 for Triple-Negative Breast Cancer. (31st May 2022) - Li, Xiajin; Ji, Yinan; Chen, Miao; Zhang, Siyi; Wang, Ziyu; Su, Danke; Luo, Ningbin
Abstract : Chemotherapy has remained the mainstay of treatment of triple-negative breast cancer; however, it is significantly limited by the associated side effects. PD-1/PD-L1 immune checkpoint inhibition therapy (ICI) has been a breakthrough for this patient population in recent years. PD-L1 expression is crucial in immunotherapy since it is a major predictor of PD-1/PD-L1 antibody response, emphasizing the significance of monitoring PD-L1 expression. Nonetheless, it is hard to assess the expression of PD-L1 before surgery, which has highlighted the urgency for a precise and noninvasive approach. Herein, we prepared a dual-mode imaging nanoparticle probe to detect PD-L1. The particle size, zeta potential, biocompatibility, and imaging ability of NPs were characterized. The synthesized NPs showed slight cytotoxicity and good T2 relaxivity. The targeted NPs accumulated more in 4T1 cells than nontargeted NPs in vitro . The in vivo experiment further demonstrated the distribution of targeted NPs in tumor tissues, with changes in NIRF and MR signals observed. Our study indicated that SPIO-aPD-L1-Cy5.5 NPs can be used to monitor PD-L1 expression in breast cancer as NIRF/MR contrast agents.